Penyuluhan Menumbuhkan Minat Berwirausaha pada Genre PIK-R Tipes Surakarta - Marjam Desma Rahadhini; Lamidi Lamidi; Sisca Dian Rahmawati; Theana Gita Reta (Jurnal Nirta : Inovasi Multidisiplin, 2025)
The community service activity titled "Counseling to Foster Entrepreneurial Interest among PIK-R Tipes Youth, Surakarta" aims to address the issue of unemployment among youth, particularly in Tipes Village, Surakarta. This initiative stems from the low percentage of entrepreneurs in Indonesia, accounting for only about 3.47% of the total population. Therefore, this effort seeks to enhance the entrepreneurial spirit among youth through counseling and mentoring as a step to create new business opportunities that can reduce unemployment rates. The activities were conducted from June to August 2024, employing methods such as preliminary surveys, team discussions, and two phases of counseling and mentoring sessions. The first phase was conducted on July 13, 2024, focusing on the importance of cultivating an interest in entrepreneurship, while the second phase was held on August 24, 2024, providing guidance on how to secure business capital. Through this program, PIK-R youth were given insights into various aspects of entrepreneurship, the importance of taking calculated risks, and effective business management techniques. The results showed an increase in the youth's understanding, knowledge, and interest in entrepreneurship. Members of PIK-R in Tipes Village became more motivated to start their own businesses by evaluating risks and utilizing available opportunities. As a follow-up, the program is planned to expand by involving MSMEs in the Solo Raya area to strengthen the impact of local economic empowerment through collaboration with the Community Service and Research Institute of Slamet Riyadi University, Surakarta. Overall, this program significantly contributed to instilling an entrepreneurial spirit, supporting economic growth, and broadening the youth's perspectives on creating independent businesses.